Business Model Innovation and Digital Transformation of the LEGO Group: An Open Innovation and Dynamic Capabilities Perspective - Elham Farahmand; Isaac Mu\~noz I Busto; Mudassir Akber Khan; Hilda Adur (International Telecommunications Society (ITS), 2024)
Digitalization is transforming industries, creating opportunities and challenges for established companies and startups (Rachinger et al., 2018). The LEGO Group, despite facing challenges, has successfully embraced digital transformation to enhance success. However, concerns about data security and ethical usage arise from extensive data collection from platforms like LEGO Ideas and Bricklinks (Holland & Wise, 2023). This research aims to address these issues and provides valuable insights from the LEGO Group's experiences to help organizations navigate their digital transformation initiatives effectively in today's digital landscape.
Keywords: 330; Business Model Innovation; Digital Transformation; Open Innovation; Dynamic Capabilities; The LEGO Group